Acido-triggered switching of the second-order nonlinear optical properties of a ferrocenyl-containing indolino-oxazolidine derivative. (January 2019) - Pielak, Kornelia; Bondu, Flavie; Sanguinet, Lionel; Rodriguez, Vincent; Castet, Frédéric; Champagne, Benoît
Abstract: The synthesis and the characterization of the linear and second-order nonlinear optical properties are reported for a new derivative of the indolino-oxazolidine family, which exploits the strong donor capacity of the ferrocenyl unit. Hyper-Rayleigh scattering experiments show that the pH-triggered switching between the closed and protonated open form of this compound enhances the first hyperpolarizability by roughly a factor 5, as a result of the increase of the push-pull π -electron conjugation within the molecule, between the donor ferrocenyl unit and the acceptor indoleninium moiety. Although derivatives exhibiting larger β responses in their nonlinear optical active form and larger β P O F / β C F contrasts were previously reported within this class of materials, the figure of merit of this ferrocenyl-based compound is high enough for device application. Quantum chemical calculations of the linear and nonlinear optical properties are at least in qualitative agreement with the experimental trends. Calculations also show that β of the protonated open form originates from two low-lying excited states, of which the contributions partly cancel each other due to the opposite directions of the photo-excited charge transfer. Highlights: pH-triggered switching between the closed and protonated open form of an indolino-oxazolidine compound bearing a donor ferrocenyl unit enhances the first hyperpolarizability by roughly a factor 5. This enhancement results from the increase of the electron conjugation within the molecule. Quantum chemical (QC) calculations of the (non)linear optical properties are at least in qualitative agreement with experiment. QC calculations show that β of the protonated open form originates from two excited states, of which the contributions partly cancel each other due to the opposite directions of the photo-excited charge transfer.